Gravures et Tapisseries Françaises. - Musée des Beaux Arts, Liège (Liège : Musée des Beaux-Arts, 1969)
Arp, Jean ; Braque, Georges ; Terk-Delaunay, Sonia ; Gilioli ; Herbin, Auguste ; Léger, Fernand ; Lurçat, Jean ; Masson, André ; Picasso, Pablo ; Rouault, Georges ; Taeuber-Arp, Sophie ; Vasarely, Victor ; Villon, Jacques
Gravures et Tapisseries Françaises, Musée des Beaux-Arts, Liège, 4-26 octobre 1969
boek